Evaluation of thyroid nodules by high resolution ultrasonography (HRUSG) and its cytological correlation in a teaching hospital (Panacea Journal of Medical Sciences, 2024)
Background: Thyroid nodules are a frequent occurrence. With the widespread use of sensitive imaging methods, a growing number of thyroid nodules are being discovered by chance. High resolution ultrasonography (HRUSG) has emerged as the most appropriate imaging modality for the assessment of thyroid nodules.Aim of the Study: To Evaluate thyroid nodules by of high resolution ultrasonography (HRUSG) and its correlation with Fine needle aspiration cytology (FNAC).Materials and Methods: Prospective study done in the department of radiology at Maheshwara medical college and Hospital, Chitkul, near Isnapur, Patancheru, Sangareddy, Telangana for duration of 3 years. A total of 80 cases were studied.HRUSG was done in all cases and Fine Needle Aspiration cytology was done. Radiological and pathological correlation was done and Sensitivity, specificify PPV, NPV and accuracy were calculated.Results: Females were predominant (62.5%) when compared to males (37.5%). Among 80 thyroid nodules , colloid nodule noted in 42.5% cases, Nodular goitre in 27.5%, Hashimotos thyroiditis and follicular adenoma in 12.5?ses and Malignancy in 5% casesConclusion: HRUSG is a sensitive and specific imaging technique that has a high level of accuracy in the evaluation of thyroid nodules. Solid composition, hypoechogenicity, taller-than-wider form, ill-defined edges, and the presence of calcification are the most effective sonographic markers for predicting cancer.